PENGGUNAAN SILIKAT TERHADAP PERTUMBUHAN UDANG VANNAME SKALA RUMAH TANGGA - Nasuki, Nasuki; Edi, Mochammad Heri; Alauddin, M. Hery Riyadi; Abrori, Mohsan; Ritonga, Lusiana BR; Primasari, Kartika; Rizky, Putri Nurhanida (Politeknik Kelautan dan Perikanan Sidoarjo, 2022)
Natural feed such as phytoplankton, contains high levels of protein, fat, and carbohydrates to enhance the growth performance and immunity in shrimp. Moreover, the presence of phytoplankton in the water column can make the waters shady so that it stimulates the shrimp to actively look for food during the day. Silicate is a macro element that used to promote the cell growth and cell wall formation of plankton. Ceraclean fertilizer product is an artificial hydrated calcium silicate with many small pores so that it is easily soluble in water to facilitate nutrient absorption by plankton cells. This study aims to determine the abundance of plankton in vaname shrimp culture ponds with the addition of ceraclean fertilizer and its correlation to the growth of vaname shrimp. This study uses a household-scale circular pond equipped with microbubble aerator technology with a power of 0.5 HP. The stocking density used was 700 fish/m3 and the maintenance period at DOC was 75. The average weight of shrimp growth at harvest was 9.8 grams with a total biomass of 273 Kg with an FCR of 1.1. A total of 262 ind/ml plankton were identified in household-scale aquaculture ponds with a percentage of Chlorophyta 57.20%, Cyanophyta 37%, Crysophyta 5%, Dinoflagellates 0.8% and Protozoa 0%. This study explains the low intake of feed used during the rearing period and the low FCR value because the shrimp utilizes natural feed. This also causes the growth of vaname shrimp in this study to continue to increase every week with an SR value of 90.1%.